Risk factor of hipernatremia in underfive with diarrhea - Candra Segeran, Candra Segeran (Universitas Gadjah Mada, 2005)
Background: Oral Rehydration Salt (ORS) solution is known as a leading therapy for diarrhea. For more than 35 year WHO and UNICEF have a single formulation of glucose-based ORS solution to prevent or treat dehydration from diarrhea. The recommended solution which provides a solution containing 90 mmol/L of sodium, 111 mmol/L of glucose with a total osmolarity 311 mOsm/I, has proven effective in wordwide use. It has been contributed substantially to the dramatic global reduction in mortality from diarrhea disease during the period. This solution is more hyperosmolar than plasma, so it can increase the risk of hypernatremia in children, especially if they do not add well as the standard of making the ORS salution. The objective: This study aims to determine whether improper mix of ORS is a risk factor for hypernatremia in children with diarrheaMethods: A case-control study was performed in this study and chi-square and logistic regression were generated in the data analysis. The sample comprised hospitalized children with acute watery diarrhea admitted at Sardjito Hospital between January 181 2002 - July 3181 2005Result: Mortality caused by hypernatremia is found in 13 children (29%) and 77% from the group have natrium level more than 155 mEq/L. Two from 12 children (12%) with Na level more than 155 mEq/L survived.Conclusion: Oral rehydration solution, formula milk, salt-glucose solutionj and dehydration state are the strong risk factors for hypernatremia.Key words: hypernatremia - risk factor - diarrhea - childrenÂ